Report on Evaluation of Consolidation of Holdings Programme Feb. 1969 - Planning Commission (Planning Commission, 1969)
At the instance of the Planning Commission, the Programme Evaluation Organisation undertook an evaluation study of the Consolidation. of Holdings Programme The study was undertaken in eight States where more than 10 lakh acres were consolidated. The sample consists of 18 districts, 36 tehsils/talukas, 106 villages and about 1100 cultivators. Consolidation measures are designed to remedy two district conditions, firstly, the division of land into under-sized units not suitable for proper cultivation and, secondly, the excessive dispersal of part of a single farm.
Programme Evaluation Organisation Government of India Planning Commission